Comparison of Various Tosylating Reagents for the Synthesis of Mono-2-O-tosyl-β-cyclodextrin - Kordopati, Golfo G.; Konstantinou, Nikoletta-Melina; Tsivgoulis, Gerasimos M. (Synthesis, 2022)
Mono-2-O-tosyl-β-cyclodextrin is a key compound, as starting material, for the preparation of multifunctional systems in supramolecular chemistry. Although several methods are available in the literature for its synthesis, yields are always moderate (usually less than 42%) and reproducibility can be an issue as a result of the difficulties encountered in its preparation that are related to selectivity, monofunctionalization, solubility and purification, among others. A modification of a literature method was developed giving emphasis to simplicity and reproducibility and, for the first time, was tested with nine easily accessible tosylating reagents that differ significantly in their nature and reactivity. Product isolation was accomplished with precipitation followed by reverse-phase flash chromatography, which is easy to scale up. Interestingly, with the proposed method, all nine reagents can be successfully applied for the synthesis of the product with yields ranging from 33% to 40%. Optimum reaction times and temperatures were found and conclusions for each tosylating reagent are drawn.
Keywords: supramolecular chemistry; cyclodextrins; tosylation; regioselectivity; sulfonates; mono-2-O-tosyl-β-cyclodextrin